Time for a European initiative for research to prevent cancer: A manifesto for Cancer Prevention Europe (CPE). (September 2018) - Forman, David; Bauld, Linda; Bonanni, Bernardo; Brenner, Hermann; Brown, Karen; Dillner, Joakim; Kampman, Ellen; Manczuk, Marta; Riboli, Elio; Steindorf, Karen; Storm, Hans; Espina, Carolina; et al.
Highlights: Effective cancer control requires public health strategies for prevention. Cancer Prevention Europe aims to transform the evidence-base for cancer prevention. A multidisciplinary network of excellence will encompass a broad research agenda. Innovative prevention research will be initiated to inform cancer control policy. A Knowledge Hub on Cancer Prevention will facilitate rapid evidence dissemination. Abstract: A landmark resolution on cancer prevention and control was adopted by Member States at the World Health Assembly 2017, noting that "risk reduction has the potential to prevent around half of all cancers" and urging "to promote cancer research to improve the evidence base for cancer prevention and control". Public health oriented strategies for cancer prevention and their optimal application in effective real-life programmes will be vital to circumvent the dramatic health and economic implications of a strategy and healthcare expenditure based primarily on cancer treatment. The inter-disciplinary nature of cancer prevention stretches from the sub-microscopic study of cancer pathways through to the supra-macroscopic analysis of the "causes of the causes", encompassing socio-economic and environmental factors. Research is required to provide new evidence-based preventive interventions and to understand the factors that hamper their implementation within health care systems and in the community. Successful implementation of cancer prevention requires long-term vision, a dedicated research agenda and funding, sustainable infrastructure and cooperation between countries and programmes. In order to develop world class prevention research in Europe that translates into effective cancer prevention guidelines and policies, we report on the creation of Cancer Prevention Europe. This international and multidisciplinary consortium of research institutes, organisations and networks of excellence with a common mission of reducing cancer morbidity and mortality in European populations through prevention, brings together different fields of expertise, from laboratory science through to policy research, as well as dissemination of the best evidence, the best quality indicators and the best practices used.